Analysis properties of Discorea hispida dennst flour (gadong flour) and its potential in bakery products - Hadi, Nur Syahirah (2018)
Discorea hispida dennst(gadong tuber) is the tuber that contain poisonous alkaloid(discorin) and the content of discorin was removed by using traditional method. The main objective of this study is to analyse the properties of gadong flour. Analysis of the properties content in gadong flour was carried out by focusing on the protein content, fat content, carbohydrate content, moisture content, ash, gluten, swelling power and water solubility. These properties are the common nutritional properties content, which is usually tested, in the commercial flour. The method to analyse each properties is by using the standard method for nutritional content in flour. The percentage content in gadong flour of each properties are moisture content 11.52%, ash content 79.9%, gluten content 19.1%, protein content 4.33%, carbohydrate 3.45% and fat 0.8%. The properties swelling power of gadong flour is 3g and water solubility is 4.2%.The gadong flour was produced from the tuber part of this plant and it have a potential in bakery products. The products that can be produced from this study are cakes and biscuits. Both cakes and biscuits were made by using 50 % Gadong flour and 100% gadong flour and 100% wheat flour as the standards. The different percentage of gadong flour used in this study is to investigate the percentage of gadong flour that can be used to replace the wheat flour in bakery products. The sensory evaluation has been performed to evaluate their acceptability in term of appearance, smell, texture, colour and taste. From the sensory evaluation, the highest acceptability of the products cake and biscuits is by using 50% gadong flour. The human sense in term of texture is very subjective which is involved their own opinion and feeling. Thus, the texture of cakes and biscuits, was analysed by using the texture analyzer from the equipment CT3 Brookfield texture analyzer. The texture of hardness, adhesiveness, fracturability, springiness, gumminess and chewiness of cake is increasing when gadong flour added in the formulation. However, the cohesiveness is decreasing when gadong flour added in the formulation. Then, for the texture analyzer of biscuit, its hardness is decreasing when gadong flour added to the formulation.